Design and Implementation of a Web-Based Student Admission Management System to Support Digital Transformation in Vocational Schools: A Case Study of SMK Ma'arif Banyumas - Rina Wati; Deni Irawan; Trisnawati Trisnawati (YHMM PUBLISHING, 2025)
The digital transformation of educational administration requires schools to adopt integrated information systems that improve efficiency, transparency, and service quality. This study aims to design and implement a web-based Student Admission Management System (SPMB) for SMK Ma'arif Banyumas to replace conventional admission procedures. The system was developed using the System Development Life Cycle (SDLC) approach, including requirement analysis, system design, implementation, testing, and evaluation. Functional verification was conducted using Black Box Testing to ensure that each module operated according to its specifications. The developed application integrates online registration, applicant profile management, document verification, admission selection, announcement publication, and automated reporting within a centralized database. The testing results indicate that all system functions performed successfully without functional errors, enabling accurate data processing and real-time information access for applicants and administrators. The implementation significantly reduced administrative workload, minimized data redundancy and input errors, and accelerated the admission process. This study contributes a comprehensive web-based admission model that supports digital governance in vocational education and provides a scalable framework for improving student admission management in secondary schools.